PENGARUH KETERIKATAN KERJA DALAM MENINGKATKAN PERILAKU KINERJA INOVATIF DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL MEDIASI : Studi Pada Guru SMP Di Kecamatan Kapuas Tengah - Oyeng Oyeng (Jurnal Bina Bangsa Ekonomika, 2023)
This study aims to test and analyze the effect of teacher work attachment on organizational commitment and innovative work behavior of teachers directly and test organizational commitment as a mediating variable. The method used in this study is quantitative research method. The sample in this study amounted to 86 respondents who were teachers at SMP Kapuas Tengah District. The data were analyzed using the Structural Equation Modeling (SEM) model using the Partial Least Square (SEM-PLS) approach. The results showed that organizational commitment proved to mediate between work attachment and innovative work behavior of teachers. Work attachment positively affects organizational commitment and innovative work behavior